Perancangan Antarmuka Pengguna Sistem Informasi Ekstrakurikuler Berbasis Web Menggunakan Balsamiq Mockups - Sani Yuliani; Sulidar Fitri; Sarmidi Sarmidi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The development of information technology encourages schools to utilize web-based information systems to support the management of extracurricular activities. However, many schools still use manual systems so that conveying information, registering members and managing extracurricular data is less effective. This research aims to design a user interface for a web-based extracurricular information system using the User-Centered Design (USD) method and Balsamiq Mockups as a medium for creating system display wireframes. The research method used includes the user needs analysis stage through observation and interviews, making wireframes, making prototypes and evaluating interface designs based on usability principles.  The results of the research are user interface designs that include login pages, dashboards, extracurricular registration, member data, attendance, student achievements and membership reports. The evaluation results of 32 respondents obtained a score of 1,448 out of a maximum score of 1,600 which is in the very good category. The implications of this research show that the interface design is expected to help users and help schools understand the flow of the system and increase the ease of use of the web-based extracurricular information system, speed up access to information, and support extracurricular data documentation in a more structured manner before the system is implemented.